The Sepsidae of the Mitaraka expedition, French Guiana (Diptera) - Silva, Vera C. [UNESP]; Pollet, Marc (Museum National d'Histoire Naturelle, Paris, France, 2020)
This paper documents on the sepsid fauna (Diptera: Sepsidae) encountered during the Mitaraka 2015 expedition. These are the first published records of Sepsidae Walker, 1833 from French Guiana. During this survey, six genera with 11 species were recorded from French Guiana for the first time: Archisepsis armata (Schiner, 1868), Archisepsis diversiformis (Ozerov, 1993), Archisepsis peruana (Ozerov, 1994), Meropliosepsis sexsetosa Duda, 1926, Microsepsis armillata (Melander & Spuler, 1917), Microsepsis furcata (Melander & Spuler, 1917), Microsepsis mitis (Curran, 1927), Palaeosepsioides erythromyrmus (Silva, 1991), Palaeosepsioides mitarakensis Silva, n. sp., described herein, Palaeosepsis Duda, 1926 and PseudopalaeosepsisOzerov, 1992. The actual state of Sepsidae taxonomy, based mostly on the male fore femur morphology and genitalic characters, has led to a case where sometimes females cannot be properly assigned to a specific taxon-this was the case here for most of the MicrosepsisSilva, 1993 females which corresponded to 25% of the collected specimens, one female assigned to Palaeosepsis dentata (Becker, 1919)/dentatiformis (Duda, 1926), and two females at present identified as Pseudopalaeosepsis sp. A checklist of Sepsidae of French Guiana is provided also including doubtful and unidentified female specimens.
Keywords: Amazon basin; biodiversity; black scavenger flies; distribution; Neotropical region; new records; new species